2004
DOI: 10.1152/japplphysiol.00751.2003
|View full text |Cite
|
Sign up to set email alerts
|

Whole body insulin resistance in rat offspring of mothers consuming alcohol during pregnancy or lactation: comparing prenatal and postnatal exposure

Abstract: This study examined the effects of maternal ethanol (EtOH) consumption during pregnancy or lactation on glucose homeostasis in the adult rat offspring. Glucose disposal was determined by minimal model during an intravenous glucose tolerance test in rats that had a small or normal birth weight after EtOH exposure in utero and in rats whose mothers were given EtOH during lactation only. All three EtOH groups had decreased glucose tolerance index and insulin sensitivity index, but their glucose effectiveness was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 44 publications
(73 reference statements)
2
37
0
Order By: Relevance
“…S I values obtained by the minimal model were consistent with the CISI values calculated from the experimental OGTT data. The minimal model analysis as a method for evaluating the glucose disposal in rats is well-established in studies (34)(35)(36)(37) in which S I was estimated by the intravenous glucose tolerance test, resulting in values similar to those observed in our investigation. Moreover, hepatic S I as calculated by HOMA-IR improved in diabetic rats just a few days after surgery, even in the presence of an increased peripheral insulin resistance due to the surgical trauma.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…S I values obtained by the minimal model were consistent with the CISI values calculated from the experimental OGTT data. The minimal model analysis as a method for evaluating the glucose disposal in rats is well-established in studies (34)(35)(36)(37) in which S I was estimated by the intravenous glucose tolerance test, resulting in values similar to those observed in our investigation. Moreover, hepatic S I as calculated by HOMA-IR improved in diabetic rats just a few days after surgery, even in the presence of an increased peripheral insulin resistance due to the surgical trauma.…”
Section: Discussionsupporting
confidence: 79%
“…Plasma GIP was measured by an enzyme immunosorbent assay kit (Phoenix Pharmaceutical Inc., Burlingame, CA): sensitivity (minimum detectable concentration) 0.44 ng/ml, intra-assay CV 5-10%, and interassay CV ,15%. Active (7,36)amide plasma GLP-1 was assessed by an enzyme immunosorbent assay kit (ALPCO Diagnostics, Salem, NH): intra-assay CV 5.36-6.60%, and interassay CV 5.51-18.87%.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…K was then calculated using least-squares linear regression as the negative slope of the natural log of glucose concentrations from 20 min to 180 min post-injection (Alder et al, 1997;Bergman et al, 1981;Chen and Nyomba, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The area under the curve was calculated using the trapezoid rule from 20-180 min post-injection and after subtraction of basal levels (Chen and Nyomba, 2004;Grottoli et al, 1997;Hatfield et al, 1999). Area under the curve (AUC) for insulin and glucagon were likewise calculated using the trapezoid rule, after subtracting basal values (Chen and Nyomba, 2004) from 10 min post-injection until the final sample. Average secretion per minute of each hormone was calculated by dividing the AUC by the duration of the sampling period, in minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of glucose homeostasis have been reported in the offspring of humans (8) and animals in association with prenatal EtOH exposure (29,47). More recently, we and others have demonstrated that EtOH consumption during pregnancy in amounts resulting in blood EtOH levels found in nonintoxicated EtOH users (46) is associated with insulin resistance, hyperlipidemia, and glucose intolerance in male rat offspring (10,11,13,18,33) without necessarily causing IUGR (12). These male rats may develop diabetes with fasting hyperglycemia during adulthood and have impaired muscle signaling in skeletal muscle (13,18,53).…”
mentioning
confidence: 90%